Influence of Laterite Bedrock on Ni Content in Langgikima District, North Konawe Regency, Southeast Sulawesi, Indonesia - Hasria; Okto, Ali; Rio Irhan Mais Cendra Jaya; Alamyah, Wa Ode Nur; Safar, Muhamad; Septiana, Sara; Syahrul (UIR PRESS, 2025)
This study investigates the influence of bedrock on nickel (Ni) content in laterite deposits in the Lameruru Region, Langgikima District, North Konawe Regency, Southeast Sulawesi Province, Indonesia. The research area is dominated by ultramafic rocks, which are potential sources of laterite nickel. The study employs literature review, field surveys for lithological data collection and representative sampling, petrographic analysis to determine mineral composition and rock types, and geochemical analysis using X-Ray Fluorescence (XRF) to determine nickel content in the rocks. The results show that the bedrock in the study area consists of harzburgite and olivine pyroxenite. Harzburgite, occupying approximately 72.72% of the area, is composed of 54-78% olivine, 15-45% orthopyroxene, 6% clinopyroxene, and accessory minerals, while olivine pyroxenite, occupying about 27.28% of the area, is composed of 27% olivine, 49% orthopyroxene, 17% serpentine, and 7% spinel. Geochemical analysis reveals that harzburgite has higher Ni content (0.10-0.16%) compared to olivine pyroxenite (0.03-0.10%). The distribution of Ni in the bedrock and saprolite is directly proportional, with higher Ni content in harzburgite in both zones. The study concludes that the type of bedrock greatly influences the nickel content in laterite deposits, with harzburgite having a higher Ni content due to its higher percentage of olivine minerals, which are the main hosts of nickel in ultramafic rocks.